Updated Oxford classification for IgA nephropathy; current status and future prospects - Hamid Nasri; Muhammed Mubarak (Society of Diabetic Nephropathy Prevention, 2019)
Since the first promulgation of Oxford classification of IgAN in 2009, various investigations have been conducted throughout the world, firstly to validate the findings of the original Oxford classification and secondly, to investigate the significance of other morphologic lesions, which were not included or studied in the original classification due to non-representation of those lesions, in turn due to restrictive inclusion criteria. PubMed, EBSCO, Embase, Web of Science, directory of open access journals (DOAJ), Scopus, and Google Scholar with keywords of IgA nephropathy, MEST scores, Oxford classification, mesangial proliferation, crescents, MEST classification, endocapillary proliferation, segmental sclerosis, interstitial fibrosis/tubular atrophy, podocytopathy, end-stage renal disease, dialysis, glomerular filtration rate, extra-capillary hypercellularity and chronic kidney disease have been searched to prepare this review. The updated Oxford classification represents a timely effort on the part of the Oxford classification Working Group for incorporation of additional pathological features not included in the original Oxford classification and it broadens the scope and extent of the pathological classification to cover the expanded spectrum of the disease. The additive impact of extra-capillary hypercellularity to the MEST scores for improved predictive power remained elusive in the original Oxford study and subsequent validation studies with similar restrictive entry criteria. The updated classification has recommended the incorporation of crescents (C) score to make the MEST classification the MEST-C classification.